Plagiarisme dalam Dunia Pendidikan: Analisis Masalah Sosial dan Urgensi Pendidikan Karakter - Kristianto Ratu Marius Naben; Heni Widyawati (Yayasan Literasi Sains Indonesia, 2024)
Plagiarism is taking someone else's work and using it in academic writing as if it were his/her own. Plagiarism is a form of moral offense and people who commit plagiarism will get criminal and civil punishment if proven to do so. Plagiarism can also be seen as a social problem in the world of education that needs to be taken seriously so that people no longer commit plagiarism. Therefore, this article aims to analyze plagiarism in education as a social problem to find the root of the problem and emphasize the importance of character building as an effort to overcome the practice of plagiarism. The research method used in this research is literature study. The author analyzed several literatures on plagiarism and character building. The important finding of this research is that plagiarism is rooted in the mentality of people who knowingly and willingly take other people's works for their own benefit even though they know that such actions are not allowed. In response to this, the author emphasizes the importance of character building as a means of forming a solid self so as not to be trapped in the practice of plagiarism. The author concludes that plagiarism is a practice that harms the dignity of education. Therefore, we must give an attention to implement character building as the basis of one's moral life to avoid plagiarism.